The Main Content And Essence Of The Game For Children Of Little Kindergarten Age - Uzokov Mukhriddin Fakhriddin ugli (Genius Publishing Group, 2023)
For children of younger kindergarten age, the main content of the game is classes with toys and substitutes. The duration of the game is short. Children of younger kindergarten age play with one or two roles and simple, unstretched plots, the features of games with the rules of this age are analyzed.
Keywords: The content of the game for children; kindergarten age; self-expression